NATURAL RESOURCES ARE THE RESOURCES OF DEVELOPMENT OF LOCAL COMMUNITIES - Bokovykova Yu.V. (Pressing Problems of Public Administration, 2017)
The directions of improvement of local government bodies’ activity considering effective using of natural resources have been determined, in particular clari cation of boundaries of settlements as location of natural resources, the consolidation of the provisions in legislation in relation to obtaining information from natural cadasters by local authorities, ensuring the implementation of public and self-control.